نظرية عند شاذلي فرحود في محتوى أغنية "القلب ومايهوى" إنشاد علي حجيج - Nuur, Khaerun Nisa; Limpo, Marwah; Saâ€™id, aely Yuliani; Nurfitriah, Aqiilah (Al-Hikmah, 2024)
This research is a study that reviews the structural analysis of the song "Al-Qolbu wa ma Yahwa" by Ali Hajiij (a structural analytical study). The research reveals the ideas, emotions, and imagination in the song " Al-Qolbu wa ma Yahwa " as well as the linguistic and musical structure of the poetry in the song. There are two objectives of this research: to understand the ideas, emotions, and imagination in the song "Al-Qolbu wa ma Yahwa" and to understand the linguistic and musical structure of the poetry in the song. The method used is descriptive qualitative by listening, collecting books, articles, and journals related to the research, and recording data from the collected sources. The results of this research show that the song "Al-Qolbu wa ma Yahwa" consists of 12 lines using structural analysis based on Shadhili Farhud’s theory, which consists of 6 elements: ideas (المعنى), emotions (العاطفة), imagination (الخيال), poetic language (لغة الشعر), musical poetry (موسيقى الشعر), and relationships between elements (علاقة بين العناصر التركيبي).